Constraints on the inner edge of neutron star crusts from relativistic nuclear energy density functionals - Moustakidis, Ch. C.; Niksic, T.; Lalazissis, G. A.; Vretenar, D.; Ring, P. (HNPS Advances in Nuclear Physics, 2019)
The transition density nt and pressure Pt at the inner edge between the liquid core and the solid crust of a neutron star are analyzed using the thermodynami- cal method and the framework of relativistic nuclear energy density functionals. Starting from a functional that has been carefully adjusted to experimental binding energies of finite nuclei, and varying the density dependence of the cor- responding symmetry energy within the limits determined by isovector prop- erties of finite nuclei, we estimate the constraints on the core-crust transition density and pressure of neutron stars: 0.086 fm−3 ≤ nt < 0.090 fm−3 and 0.3 MeV fm−3 < Pt ≤ 0.76 MeV fm−3 [1].